(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to United Nations estimates, disabled people make up 10% of the world’s population, which causes a number of moral, social and economic problems, the level of their resolution is one of the most important features of modern society. Among childhood disabilities, diseases of the nervous system - 19.5%, mental diseases - 14.3% and congenital anomalies - 21% prevail. In 60% of cases, neurological disability in childhood is associated with the pathology of the perinatal period, while 24% are patients with cerebral palsy. Every third child in the Russian Federation has various neuropsychic diseases, 80% of which are caused by perinatal factors, which determines the high social importance of this problem. Perinatal lesions of the nervous system represent a large group of pathological conditions combined with the time of negative impact on the fetus and newborn. The perinatal period begins from the 22nd full week of intrauterine life of the fetus and ends 7 days after birth. Intranatal - the period during childbirth. Neonatal - includes 28 days after birth. Embryo - from the time of conception to 10 weeks. Embryopathy is a defect between the 16th day after fertilization and the end of the 10th week of pregnancy. Fetopathy - damage from 11 weeks to the end of birth. (Professor EV Shnitkova. 2022).